The watchmaker of Filigree Street - Pulley, Natasha (Bloomsbury, 2015)
In 1883, Thaniel Steepleton returns to his tiny flat to find a gold pocketwatch on his pillow. But he has worse fears than generous burglars; he is a telegraphist at the Home Office, which has just received a threat for what could be the largest-scale Fenian bombing in history. When the watch saves Thaniel's life in a blast that destroys Scotland Yard, he goes in search of its maker, Keita Mori--a kind, lonely immigrant who sweeps him into a new world of clockwork and music. Although Mori seems harmless at first, a chain of unexpected events soon proves that he must be hiding something. Meanwhile, Grace Carrow is sneaking into an Oxford library dressed as a man. A theoretical physicist, she is desperate to prove the existence of the luminiferous ether before her mother can force her to marry. As the lives of these three characters become entwined, events spiral out of control until Thaniel is torn between loyalties, futures and opposing geniuses. Utterly beguiling, The Watchmaker of Filigree Street blends historical events with dazzling flights of fancy to plunge readers into a strange and magical past, where time, destiny, genius--and a clockwork octopus--collide.